2015
DOI: 10.1038/cr.2015.146
|View full text |Cite
|
Sign up to set email alerts
|

Multiple amino acid sensing inputs to mTORC1

Abstract: The evolutionarily conserved target of rapamycin complex 1 (TORC1) is a master regulator of cell growth and metabolism. In mammals, growth factors and cellular energy stimulate mTORC1 activity through inhibition of the TSC complex (TSC1-TSC2-TBC1D7), a negative regulator of mTORC1. Amino acids signal to mTORC1 independently of the TSC complex. Here, we review recently identified regulators that link amino acid sufficiency to mTORC1 activity and how mutations affecting these regulators cause human disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
169
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(179 citation statements)
references
References 121 publications
(189 reference statements)
3
169
0
1
Order By: Relevance
“…This work adds a significant new dimension to the paradigm in which mTOR is mostly studied for its activation by growth factor-activated membrane receptors and nutrient availability (Menon and Manning 2008;Laplante and Sabatini 2013;Shimobayashi and Hall 2016). Furthermore, specific inhibition of RNA Pol II-driven transcription demonstrated that cytoplasmic mTOR activity alone is not sufficient for the androgenmediated rewiring of PCa cell metabolism.…”
Section: Discussionmentioning
confidence: 98%
“…This work adds a significant new dimension to the paradigm in which mTOR is mostly studied for its activation by growth factor-activated membrane receptors and nutrient availability (Menon and Manning 2008;Laplante and Sabatini 2013;Shimobayashi and Hall 2016). Furthermore, specific inhibition of RNA Pol II-driven transcription demonstrated that cytoplasmic mTOR activity alone is not sufficient for the androgenmediated rewiring of PCa cell metabolism.…”
Section: Discussionmentioning
confidence: 98%
“…The serine/threonine protein kinase TOR (target of rapamycin) is a central regulator of ribosome biogenesis. Both yeast and mammalian cells have two functionally different TOR complexes, TOR complex 1 (TORC1) and TOR complex 2 (TORC2); TORC1 is stimulated by amino acid sufficiency, and it responds to rapamycin to generate responses akin to those elicited by starvation and environmental stress such as hypoxia and DNA damage to reduce cell growth (180,181). TORC2 is rapamycin insensitive and controls the organization of the actin cytoskeleton (181)(182)(183).…”
Section: Hmo1 Coordinates Responses To Torc1 Signalingmentioning
confidence: 99%
“…Amino acid transporters mediate the exchange of amino acids from extracellular to intracellular space as amino acid carriers, with some acting as amino acid sensors (37). Solute carriers (SLCs) that transport amino acids across the plasma membrane include SLC family 7, member 5 (SLC7A5); SLC3A2; and SLC1A5 (38). Amino acids can activate the Rag GTPases directly (26).…”
Section: Upstream Regulation Of Mtorc1 By Nutrients and Other Factorsmentioning
confidence: 99%